Clinacanthus nutans (Burm. f.) Lindau Extract Inhibits Dengue Virus Infection and Inflammation in the Huh7 Hepatoma Cell Line - Kanyaluck Jantakee; Suthida Panwong; Pachara Sattayawat; Ratchaneewan Sumankan; Sasithorn Saengmuang; Kiattawee Choowongkomon; Aussara Panya (MDPI AG, 2024)
Dengue virus (DENV) infection has emerged as a global health problem, with no specific treatment available presently. Clinacanthus nutans (Burm. f.) Lindau extract has been used in traditional medicine for its anti-inflammatory and antiviral properties. We thus hypothesized C. nutans had a broad-ranged activity to inhibit DENV and the liver inflammation caused by DENV infection. The study showed that treatment using C. nutans extract during DENV infection (co-infection step) showed the highest efficiency in lowering the viral antigen concentration to 22.87 ± 6.49% at 31.25 μg/mL. In addition, the virus-host cell binding assay demonstrated that C. nutans treatment greatly inhibited the virus after its binding to Huh7 cells. Moreover, it could remarkably lower the expression of cytokine and chemokine genes, including TNF-α, CXCL10, IL-6, and IL-8, in addition to inflammatory mediator COX-2 genes. Interestingly, the activation of the NF-κB signaling cascade after C. nutans extract treatment was dramatically decreased, which could be the underlying mechanism of its anti-inflammatory activity. The HPLC profile showed that gallic acid was the bioactive compound of C. nutans extract and might be responsible for the antiviral properties of C. nutans. Taken together, our results revealed the potential of C. nutans extract to inhibit DENV infection and lower inflammation in infected cells.